2016
DOI: 10.1016/j.hlpt.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical price comparisons across the European Union and relative affordability in Cyprus

Abstract: This paper performs price comparisons of branded pharmaceutical products in markets of eleven European Union countries. We follow a Laspeyres index approach, using Cyprus as the base country and analyse prices in the private and public markets and also consider biotechnology products separately. We find that Germany, Denmark and Austria demonstrate the highest pharmaceutical prices in the EU, followed by Cyprus. When adjusting for per capita income, Cyprus demonstrates the highest prices. Given that there is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This "basket index" field is still discussed and amended today as an intertemporal application, e.g., with questions regarding testing and quality evaluation of price indices [79,80]; (ii) The second area of index number application in economics is further intertemporal comparisons of organizational or industry quantities such as indexed economic cycle growth and development indices or forecasts [81]; (iii) The third area applies the use of index numbers for an interorganizational or geographical comparison of economic quantities such as production outputs between different corporations or commodity prices between different trading locations and stock markets [82,83]. This third application area has to be connected to the index number application in question here, which is the interorganizational comparison of university performance measures within ranking systems.…”
Section: Research Methodology and Index Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…This "basket index" field is still discussed and amended today as an intertemporal application, e.g., with questions regarding testing and quality evaluation of price indices [79,80]; (ii) The second area of index number application in economics is further intertemporal comparisons of organizational or industry quantities such as indexed economic cycle growth and development indices or forecasts [81]; (iii) The third area applies the use of index numbers for an interorganizational or geographical comparison of economic quantities such as production outputs between different corporations or commodity prices between different trading locations and stock markets [82,83]. This third application area has to be connected to the index number application in question here, which is the interorganizational comparison of university performance measures within ranking systems.…”
Section: Research Methodology and Index Numbersmentioning
confidence: 99%
“…[51][52][53] and [56] (pp. [80][81][82][83][84][85][86]). Institutions provide and sign off their institutional data for use in the THE ranking.…”
Section: 00%mentioning
confidence: 99%
“…Conversely, they also observed that prices in some middle-income countries were lower than in certain low-income countries. In an analysis of drug prices in 11 European Union member states, Petrou and Vandoros (2016) found that income levels had no consistent bearing on drug prices across countries.…”
Section: Differential Pricing: Theoretical Backgroundmentioning
confidence: 99%
“…Payments for pharmaceuticals account for the highest share of OOP payments, making up 14.1 % of total health spending compared to just 5.5 % for the EU (Figure 13). Cyprus has the highest pharmaceutical prices in the EU when prices are adjusted for per person income (Petrou & Vandoros, 2016). To ensure access to medicines, from June 2019, under the new General Healthcare System, beneficiaries pay a flat co-payment of only EUR 1 for the cheapest generic equivalent of a prescribed medicine.…”
Section: Pharmaceuticals Take the Largest Share Of Out-of-pocket Spen...mentioning
confidence: 99%